Game Theory Analysis of the Trade War between United States and China - Pandey, Ashok Raj (Rural Development Journal, 2019)
The paper begins with account of US-China trade and gradually digs out the historical beginning of trade war between two countries. Then the paper examines some chronological context from past which triggered US to impose tariff in modern time. In second section the paper attempt to adapt and analyse trade war from game theory perspective with particular focus on the Nash equilibrium’s decision analysis model of prisoner's dilemma. Thirdly the research progress to argue trade was as lose-lose game where both country will experience economic as well as political setbacks. Also this research gives some acute evidences to show US as more vulnerable amid this trade war and it’s prone to get more hit than china if trade war continues. Ultimately our study finds that the best solution of trade was is to stop the war itself and both country need to come under table talk to discuss each other’s dissatisfaction and solve it in institutional way.